Strategi Pemasaran Mangga Klonal 21 di Kabupaten Pasuruan - Nur Yunita Puspitasari; Wahyu Santoso; Hamidah Hendrarini (Program Studi Agribisnis, Fakultas Pertanian, 2021)
Tujuan penelitian ini guna mengetahui strategi komunikasi pemasaran yang tepat pada sentra budidaya mangga klonal 21. Data dikumpulkan melalui tahap observasi dan wawancara mendalam kepada petani mangga klonal 21 menggunakan kuisioner. SWOT digunakan untuk menentukan strategi yan tepat dalam memasarkan mangga klonal 21 berdasarkan faktor internal dan eksternal. Strategi yang tepat sesuai SWOT berupa melakukan diversifikasi produk guna menaikkan penjualan revenue secara signifikan. Strategi diversifikasi yang dapat diterapkan pada komunikasi pemasaran yakni mengembangkan promosi di media sosial dengan memanfaatkan e-commerce seperti shopee dan website resmi mangga klonal 21 sehingga konsumen akan mengetahui informasi dari pemasaran tersebut. Matriks QSPM digunakan untuk mengetahui alternatif strategi yang akan digunakan. Alternatif strategi tersebut berupa melakukan pengembangan off season guna memenuhi permintaan pasar. The purpose of this study was to determine the right marketing communication strategy at the clonal 21 mango cultivation center. The data collection method used quantitative descriptive with the stages of observation, interviews and the use of SWOT questionnaires to clonal 21 mango farmers which was used to determine the right strategy in marketing clonal 21 mango based on internal and external factors. The sampling technique used was purposive sampling method which used non-random sampling with a population of 120 farmers who used a sample of 50 farmers because they were still members of one Gapoktan. The right strategy according to SWOT is to diversify products to increase revenue sales significantly. Diversification strategies that can be applied to marketing are developing processed products made from clonal 21 mangoes and using social media as a marketing medium to attract consumer buying interest while outside Pasuruan Regency. The QSPM matrix is ​​used to find out the alternative strategies to be used. The alternative strategy is conducting off season development to meet market demand and developing processed products by prioritizing the quality of human resources in the form of using technology to support the quality and quantity of clonal mangoes.